Environmental Accounting in Marine Protected Areas: the EAMPA Project - Franzese, Pier Paolo; Buonocore, Elvira; Paoli, Chiara; Massa, Francesco; Stefano, Donati; Fanciulli, Giorgio; Miccio, Antonino; Mollica, Emanuele; Navone, Augusto; Russo, Giovanni F.; Povero, Paolo; Vassallo, Paolo (Journal of Environmental Accounting and Management, 2026)
The EAMPA project is a research programme focused on the implementation of an environmental accounting system for all the 29 Italian Marine Protected Areas (MPAs). The main goal of such a system is the calculation of the ecological and economic value of the MPAs, with particular reference to the ecosystem services generated in each protected area. Environmental and economic costs as well as the impacts related to human activities in the MPAs will be also assessed. Finally, an overall balance and the assessment of net benefits will be calculated. To reach this goal, a multicriteria environmental accounting system will be implemented following a standardized protocol of assessment. The outcomes of the project will be managed through an operational WebGIS platform capable of spreading user-friendly information to local managers, policy makers, and other stakeholders. The environmental accounting system will be structured to be updatable over time, thus representing a useful tool for the management of the MPAs in the years to come. Moreover, the research programme represents a unique opportunity to establish a collaborative network among all Italian MPAs. Finally, the outcomes of the project will be also functional to other important and timely processes dealing with the study and protection of European marine ecosystems, such as the Marine Strategy Framework Directive.